Metodología para la gestión del alcance, estimación del costo y tiempo para Proyectos Ágiles en la Agencia Digital PIXEL - Tinoco-Torres, Joel (Instituto Tecnológico de Costa Rica, 2016)
Agile methodologies are a new way of developing products consisting of iterative development, customer feedback, well-structured teams, and deployment flexibility. In recent decades, these methodologies have been positioned as an alternative for managing IT projects and have been adopted by a large number of successful companies. This research work is performed in the Digital Agency, Pixel Design Costa Rica, a web development company. A methodology for managing scope, cost estimate and time estimate for your agile projects is proposed, as it seeks to resolve the current management deficiencies in this field and increase the success of the company by providing products of value to their end customers. An analysis of project management and traditional methodologies it is performed in this research, and it elaborates on agile methodologies in order to create a conceptual framework for the proposed work. The current situation of the company is defined as the key points of research. Among the main findings obtained, during the years 2014 to early 2016, the effective scope management accomplishment is 73%, followed by 65% of the effective cost management and with the lowest score is 45% of the effective time management. These results are alarming for the company because they reflect the estimated time and cost are factors causing heavy losses in the company. The documentary analysis is performed within the enterprise sector to identify the best practices and tools according to Agile methodologies. A list of 26 recommended practices and 4 possible software tools to manage agile projects are obtained. These inputs help to determine SCRUMBAN as the basis to provide to PIXEL a methodology for managing scope, estimate cost and time for agile projects. The processes, inputs, outputs and interaction of the methodology for the company are exposed and detailed to achieve the objective of the research. xiv It is recommended that prior the implementation, the organization promotes the training in the agile methodology proposed to meet the profiles of leading roles such as SCRUM Master, also search to proceed with the implementation incrementally in their projects, defining the scope and estimate the time and cost gradually. It is also of great importance that key concepts like, Done Criteria and Work in Progress in conjunction with tools like ActiveCollab© and Kanban Board, are present in the company and exposed to the stakeholders in order to search the proper application when running the agile projects.
Proyecto de Graduación (Maestría en Gerencia de Proyectos) Instituto Tecnológico de Costa Rica, Escuela de Ingeniería en Construcción, Escuela de Ingeniería en Computación, Escuela de Administración de Empresas, 2016.
Keywords: Scrum; Scrumban; Costo; Tiempo; Agencia digital